Pseudoappendicitis caused by Plesiomonas shigelloides. - Fischer, K (1988)
A 20-year-old patient was hospitalized with clinical signs of acute appendicitis. After surgery, the histological findings in the appendix and a lymphatic node suggested the diagnosis of pseudoappendicitis caused by Plesiomonas shigelloides, which was isolated in pure culture from the lymphatic node. The strain of P. shigelloides was found to elaborate a heat-stable toxin and harbored two plasmids of 280 and 4 kilobases. A large plasmid has previously been implicated as a virulence marker in P. shigelloides infections.